UPAYA GURU KELAS DALAM MENGATASI PERILAKU KENAKALAN SISWA DI KELAS V SDI LABAT KOTA KUPANG - Nahak, Maria Yovita Luruk; Koro, Maxsel; Adoe, Treesly Y.N (SINERGI : Jurnal Riset Ilmiah, 2025)
This research was conducted at SDI Labat, Kupang City with research results showing that the forms of student delinquency are ordinary delinquency, delinquency that leads to criminal offenses, conscious and deliberate delinquency and unconscious and unintentional delinquency. The factors that cause student delinquency are family factors, namely parents are busy with work so they cannot pay attention and look after their children directly, the family economy is very poor so that children's needs are not met, and there is no continuity between the family and the school environment such as work. Community environmental factors, namely without parental supervision in playing. School environmental factors where students are surrounded by families with different characters, so that in school often results in things that are not good for moral development which causes delinquency. Efforts made to overcome students' delinquent behavior include verbal warnings, special attention, habituation, providing rules and creating interesting and creative learning activities..